Praise And Thanksgiving And The Relationship Between Them In The Light Of The Linguistic Lexicon And The Holy Qur’an - Hassansayedalı, Ola (Fırat University, 2022)
This research aims to determine what is meant by the terms Praise and thanksgiving the difference between them, and the relationship that brings them together in the light of Arabic dictionaries and the Holy Qur’an. This research also aims to show the extent to which the relationship between praise and thanksgiving has been affected by the transition from the limited linguistic framework to the horizons of the Holy Qur’an. This research is based on a combination of induction, analysis and conclusion. Among the most important findings of the research are the following: First- Praise and thanksgiving are not synonymous linguistically or idiomatically. Second- The relationship between Praise and thanksgiving in linguistic dictionaries is about generality and particularity relationship; and it is the same in the Holy Qur’an, but that relationship has revolved in linguistic dictionaries in a limited horizon. However, when I studied the difference from Quranic perspective, I found a wider range of differences, not limited by time or place and the aspects of that relationship multiplied. Third- Praise (to Allah Almighty) is for the blessings He has bestowed upon us, and for the attributes of perfection with which He has been characterized. As for thanksgiving, it is only for the blessing.

Bu araştırmanın amacı hamd - şükür kavramlarının manalarını, farkını, Arapça sözlüklerin ve Kur'ân-ı Kerîm'n ışığında aralarında ne tür bir ilişkinin bulunduğunu, bu ilişkinin sözlük bilgisi sınırlarında çıkıp Kur'ân-ı Kerîm'in derin anlamları içine girdiğinde ne boyutta değişikliklere uğradığını göstermektir. Çalışmada bilimsel araştırma, analiz ve sentez yöntemleri kullanılarak şu temel sonuçlara ulaşılmıştır. Bunlardan birincisi, hamd - şükür kavramlarının ne dil ne de kavramsal boyutta eş anlamlı olmadığıdır. İkincisi, hem sözlüklerde hem de Kur'ân-ı Kerîm'de hamd - şükür ilişkisi umum-husus ilişkisi olarak ele alınmıştır. Ancak sözlükler konuyu çok dar çerçevede ele alırken Kur'ân-ı Kerîm zaman ve mekân sınırlarını aşan bir tarazda çok geniş boyutlara taşımıştır. Üçüncüsü, hamd nimetlerin ötesinde Allah'a yapılan ve onun kemal sıfatlarıyla ilişkili bir övgüdür. Şükür ise sadece nimetler karşılığında yapılan bir teşekkürdür. Dördüncüsü, şükür hem söz hem de fiille olurken hamd sadece sözle olur. Beşincisi, sözlükler hamd kelimesini hem Allah'a hem de diğer varlıklara yönelik kullanırken Kur'an-ı Kerîm onu sadece Allah Teâlâ'ya hâs kullanmıştır
Arapça Sözlükler ve Kurân-ı Kerîm Işığında Hamd-Şükür Kavramları ve Aralarındaki İlişki
Keywords: Religious Studies; Din Araştırmaları